The Effect Of Student Team-Achievement Division (STAD) Technique On The Students’ Speaking Ability Of Grade Eight Of SMP Negeri 2 Pematangsiantar - Situmorang, Gracela Emylia; Napitupulu, Selviana; Siahaan, Basar Lolo (Innovative: Journal Of Social Science Research, 2025)
This research was carried out to find out whether the affect of Student Team-Achievement Division Technique on students’ comprehension in speaking ability at grade VIII of SMP Negeri 2 Pematangsiantar. The research methodology used in this research was a quantitative method with a quasi-experimental. The population of this research was grade VIII of SMP Negeri 2 Pematangsiantar in the academic year 2023/2024. The researcher took two classes as the sample. The samples were VIII-10 as experimental group consisted of 32 students and VIII-11 as control group consisted of 32 students. The experimental group was taught by student team-achievement division technique meanwhile control group was taught by conventional technique. The data were obtained by using pre-test and post-test given to both groups. The experimental class mean score on the pre-test was 44,40 and the mean score of control class was 58,40. On the other hand, the mean of variabe in experimental class on post-test was 74,93, while the mean score of control class on post-test was 66,56. To acquire data, the researcher used test as instrument. The result of t-test was 9,885 which was higher than t-table at 5% of level significance (1,670). The result of significance value indicates that alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. It meant that there was significant effect by using Student Team-Achievement Division Technique at Grade Eight of SMP Negeri 2 Pematangsiantar.